2017
DOI: 10.1159/000485753
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Effects of the Antiepileptic Drug Valproic Acid in Glioblastoma

Abstract: Background/Aims: Valproic acid (VPA), an anticonvulsant and mood-stabilizing drug is used to treat epileptic seizure of glioblastoma patients. Besides its antiepileptic activity, VPA has been attributed further functions that improve the clinical outcome of glioblastoma patients. Those comprise the inhibition of some histone deacetylase (HDAC) isoforms which reportedly may result in radiosensitization. Retrospective analysis of patient data, however, could not unequivocally confirm a prolonged survival of glio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…This can be explained with a higher negative physiological membrane potential in U251 as compared to T98G cells since the higher the physiological membrane potential the more positive clamp voltage is required to reach the activation voltage of the channel. Most importantly, K + selectivity, high unitary conductance, and voltage dependence of the TTFields-induced channel were identical to the characteristics of paxilline-sensitive BK K + channels reported earlier to be highly expressed in T98G and U251 cells [45].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…This can be explained with a higher negative physiological membrane potential in U251 as compared to T98G cells since the higher the physiological membrane potential the more positive clamp voltage is required to reach the activation voltage of the channel. Most importantly, K + selectivity, high unitary conductance, and voltage dependence of the TTFields-induced channel were identical to the characteristics of paxilline-sensitive BK K + channels reported earlier to be highly expressed in T98G and U251 cells [45].…”
Section: Resultssupporting
confidence: 77%
“…Taking into account that cell cycle [57], cell migration [38,45,57], brain infiltration [40], cell death programming [57], DNA repair and radioresistance [42,57] of glioblastoma cells have been demonstrated to be regulated by Ca 2+ -dependent signaling pathways [58] an interference of TTFields with glioblastoma biology can be expected. In line with this assumption, the present study demonstrated that TTFields indeed interfered with all cell biological parameters tested.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our observation, Eckert et al . 2017 showed that VPA had only small anti-proliferative effects on human GBM cell lines, but the authors were unable to detect an impairment of survival or a lower radioresistance of temozolomide-treated primary spheroid cultures [46]. When used in dose escalation experiments that excess patient plasma levels [5], one may find inhibitory effects by VPA [4750].…”
Section: Discussionmentioning
confidence: 99%
“…The molecular biology of GBM is highly heterogeneous. Despite advances in the technical proficiencies of surgical and radiation oncology, patients with GBM have a poor prognosis, with a median survival of less than one year from the time of diagnosis and a five-year mortality of over 95% [5][6][7]. To date, the pathogenesis of GBM is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%